A Survey on Security Issues in Cloud Computing - V, Pushpalatha; K B, Sudeepa; H N, Mahendra (International Journal of Engineering and Technology, 2018)
Cloud computing is an approach to elaborate the limit and adding the endowment without adding the resourcesinto the modern framework, organizing new process, or authorizing new programming. Cloud computing is the major outcome of the composition of the traditional enrolling development and system development like matrix multiplication, distributed computing, parallel computing and etc. The cloud computing will allows the information allocation that consists of software, policy and infrastructure, which defines the virtualization. Cloud computing is the design which provides the services through internet on paper use access to store the information like storage, servers and applications, without its physical existence. This paper gives outlines that what is meant by the cloud computing means, various cloud computing models such as cloud deployment model, and the cloud service models and the security issues that is faced by the cloud computing model, and the various existing security solutions. This paper is a survey of security issues and security challenges in the world of cloud computing which provides the various aspects of cloud computing.Â Â